Local-plus approach: Does it help improve the satisfaction of returnees? An empirical study in the perspective of social comparisons - Song, Lingfang (Management international / International Management / Gestiòn Internacional, 2023)
Returnees are valuable managerial and technical assets for multinationals (MNCs). To motivate and retain them, some companies adopt the local-plus approach to remunerate them. This study explores returnees’ satisfaction with the local-plus approach and attempts to identify key factors influencing their satisfaction. The study revealed that returnees’ satisfaction with the approach varies significantly. Their satisfaction does not always correlate with the interests of the packages. From the perspective of social comparisons, four factors influencing returnees’ satisfaction were identified: self-identity, self-esteem, company policy, and expats’ conditions.